Performance Testing of Five Back-End JavaScript Frameworks Using GET and POST Methods - I Putu Agus Eka Pratama (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Currently, JavaScript is widely used in server-side (Back-End) website development. There are five choices of Back-End JavaScript frameworks that are commonly used: Koa, Express, Plumier, Loopback, Nest. Developers need to choose which framework has the best performance in order to produce a website with the best performance. For this reason, in this research, a comparsion of performance of the five Back-End JavaScript frameworks on the HTTP protocol was carried out using the GET and POST methods. Performance measurement uses two assessment parameters: 1.) The framework's ability to handle requests per second (req/s), 2.) Decrease in data processing speed (%) related to parsing, validation, routing, requests. Each tested framework is equipped with a router, body-parser, validator, NPM. Tests were carried out ten times on GET and POST, then obtain the average performance value of each framework. The test results show that Koa has the best performance and Loopback has the worst. From the results, it is recommended that Koa, Express, Plumier, be chosen by the developer, compared to Nest and Loopback.